Using a configurable EMR and decision support tools to promote process integration for routine HIV screening in the emergency department. (2nd September 2015) - McGuire, Robert; Moore, Eric
Abstract: Given the clinical and public health benefits of routine Human Immunodeficiency Virus (HIV) testing in the emergency department (ED) and Centers for Disease Control and Prevention recommendations, Maricopa Medical Center, as part of Maricopa Integrated Health System, started Test, Educate, Support, and Treat Arizona (TESTAZ) and became the first and, to-date, only hospital in Arizona to implement routine, non-targeted, opt-out, rapid HIV screening in the ED. The authors describe the implementation of a universal, routine, opt-out HIV screening program in the adult ED of an urban safety-net hospital serving under-served populations, including the uninsured and under-insured. Through a controlled and collaborative process, the authors integrated custom documentation elements specific to HIV screening into the triage/intake process, implemented and utilized clinical decision support tools to guide clinicians in each step of the process, and used electronic data collection and reporting to drive new screening protocols that led to a significant increase in overall HIV testing rates.